Anxiety, Depression, and Disability Across the Lifespan - Brenes, Gretchen A. (2008)
The authors examined the relationship between anxiety, depression, and physical disability, after controlling for demographic and health variables, in a sample of 374 adults ages 18-94. Results indicate that anxiety, depression, and comorbid anxiety and depression are associated with higher levels of disability, after controlling for factors such as age, gender, income, self-rated health, number of medical conditions, and number of physician visits in the past year. Furthermore, anxiety, depression, and comorbid anxiety and depression have a differential effect on disability according to age, with older adults with any of these symptoms reporting higher levels of disability than younger adults. These findings suggest that physicians working with older adults should assess for and treat anxiety as well as depressive symptoms.